2006
DOI: 10.1111/j.1944-9720.2006.tb02899.x
|View full text |Cite
|
Sign up to set email alerts
|

Stepping Out of the Comfort Zone: Profiles of Third‐Year Spanish Students' Attempts to Develop Their Speaking Skills

Abstract: This qualitative study focused on the learning experiences of four third‐year Spanish students enrolled in a college‐level Spanish composition and conversation course. The study provided insights into the impact of expanding out‐of‐class opportunities to engage in communicative tasks through the use of streamed feature films, online chats, and video journal assignments on the development of higher levels of oral proficiency. Data sources included transcripts of in‐class and out‐of‐class speaking assignments, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Voller and Widdows (1993) and Joiner (1990) cautioned instructors to avoid slow-moving films that contain frequent monologues and that require detailed background knowledge. In a previous study (Bueno, 2006), I also reported that learners find monologues highly charged with emotion and action-packed scenes particularly difficult to comprehend. When films do not meet all of these criteria, or when they contain some of the challenges described above, instructors must find ways to scaffold aural comprehension.…”
Section: What We Know About Integrating Film In Foreign Language Coursesmentioning
confidence: 83%
See 3 more Smart Citations
“…Voller and Widdows (1993) and Joiner (1990) cautioned instructors to avoid slow-moving films that contain frequent monologues and that require detailed background knowledge. In a previous study (Bueno, 2006), I also reported that learners find monologues highly charged with emotion and action-packed scenes particularly difficult to comprehend. When films do not meet all of these criteria, or when they contain some of the challenges described above, instructors must find ways to scaffold aural comprehension.…”
Section: What We Know About Integrating Film In Foreign Language Coursesmentioning
confidence: 83%
“…With today's technology, instructors can utilize these instructional strategies more effectively and efficiently to mitigate the difficulty in comprehending feature films for learners. In regard to the delivery of feature film, course management systems allow instructors to show the film in segments appropriate for the proficiency level of the students and to include judiciously first language and target language captions (Bueno, 2006;Markham, 1989Markham, , 1999Nicholas & Toporski, 1993;Stewart & Pertusa, 2004).…”
Section: What We Know About Integrating Film In Foreign Language Coursesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on the use of technology in second/foreign language teaching focused on: the effectiveness of the computer-mediated communication as a learning and teaching resource (Ramzan & Saito, 1998); the use of a telecollaborative learning environment (Belz & Kinginger, 2002); audiographic conferencing (Hampel, 2003); electronic discussion (Hanna & de Nooy, 2003); synchronous chat systems used to explain technical concepts to student (Day, Wood, Scutter & Astachnowicz, 2003); online role plays ( Milton, 2004); students use of electronic course supplements, such as film to improve their levels of proficiency (Bueno, 2006); the development of a tool to evaluate oral tests (Laborda, 2006); the use of computer technology in the assessment (Hunt, Neill & Barnes, 2007); problems and strategies in oral communication tasks (Lam, 2007); online interaction with native speakers (Lee, 2004;Mahfouz & Ihmeideh, 2009); Learners' scaffolding using social network service (Christensen, 2010); and video presentation on students' blogs to enhance public speaking skills (Shih, 2010).…”
Section: Introductionmentioning
confidence: 99%